ENHANCE AN AUTOMATIC SCHEDULING SYSTEM USING IOT - Yoffi Andinanta (Jurnal Scientia, 2023)
Currently, student attendance is still mostly done manually. This wastes time and energy, besides the problem that occurs is that errors often occur when recording absences at the end of each month. Nowadays, there are new technologies in the form of programmable ICs, namely microcontrollers. The microcontroller is filled with programs by humans so that a system can work automatically and can replace the role of humans in carrying out an activity. With the presence of a microcontroller, the author can overcome the above problems that occur in student attendance and calculating the compensation value for student absences each year. The microcontroller used is an Arduino Atmega328 which functions to process and manipulate input and control output. The input processed is an RFID card containing the student's name as a condition for entering the class.